Power minimization under throughput management over wireless networks with antenna diversity. - Zhu Han (IEEE Transactions on wireless communications)
In multiaccess wireless communication systems, power control and adaptive modulation are two important means to increase spectral efficiencies, combat time-varying fading channels, and reduce cochannel interferences. The overall uplink transmitted power is minimized under the constraints that there is no reduction in overall network throughput and each user achieves the desired time-average throughput. Adaptive M-QAM modulations with two kinds of antenna diversity are considered. Each user can select a range of modulation rates, according to his channel condition and transmission history. Two subproblems are considered for the development of suboptimal low-complexity adaptive algorithms. First, at the user level, the following needs to be determined: the range of modulation rates that each user can accept at a specific time to ensure fairness. Then, each time at the system level, within the acceptable ranges, the system finds out what throughput allocation for different users requires the lowest overall transmitted power. The scheme can be interpreted as "water filling" each user's throughput in time domain and allocating network throughput to different users at each time. From the simulation results, the proposed scheme reduces the overall transmitted power up to 7 dB and increases average spectral efficiency up to 1.2 bit/s/Hz, compared with the previous known power control schemes.